1. ## algebraic expressions

-(12/-3) +5(2) = -4+10 =6 my study book tells me this equation = -6 can anyone tell me why and how this equation could = -6

2. Originally Posted by Leona_Marie
-(12/-3) +5(2) = -4+10 =6 my study book tells me this equation = -6 can anyone tell me why and how this equation could = -6
$\displaystyle -\left(\frac{12}{-3}\right) + 5 \cdot (2) = -(-4) + 10 = 4 + 10 = 14$

Could it be that the original question reads:

$\displaystyle -\left(\frac{12}{-3}\right) + 5 \cdot (-2) = -(-4) - 10 = 4 - 10 = -6$

3. Originally Posted by earboth
$\displaystyle -\left(\frac{12}{-3}\right) + 5 \cdot (2) = -(-4) + 10 = 4 + 10 = 14$

Could it be that the original question reads:

$\displaystyle -\left(\frac{12}{-3}\right) + 5 \cdot (-2) = -(-4) - 10 = 4 - 10 = -6$
earthboth, what if we did-(12/-3 +2)^2

4. Originally Posted by Leona_Marie
earthboth, what if we did-(12/-3 +2)^2
Of course, that is possible too. But there are some more possibilities, for instance:

$\displaystyle -\left(\frac{12}{-3} +5(2)\right) = -(-4+10) = -6$

5. Originally Posted by earboth
Of course, that is possible too. But there are some more possibilities, for instance:

$\displaystyle -\left(\frac{12}{-3} +5(2)\right) = -(-4+10) = -6$
thank you very much,